2019
DOI: 10.1039/c8ra10547b
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of FOXO6 inhibits cell proliferation and ECM accumulation in glomerular mesangial cells cultured under high glucose condition

Abstract: Forkhead box O 6 (FOXO6), a FOX transcription factor, has been found to be involved in diabetes mellitus and related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…According to literature reports, FOXO6 can activate the phosphoinositide 3-kinase (PI3K)/serine-threonine kinase (AKT) signaling pathway, thereby promoting cell proliferation and inhibiting apoptosis ( Feng and Qiu, 2018 ; Wang et al, 2019 ; Wu et al, 2020 ). Meanwhile, KEGG enrichment analysis suggested that FTO is involved in the pathogenesis of CGN through PI3K/AKT signaling pathway ( Supplementary Figure S3B and Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to literature reports, FOXO6 can activate the phosphoinositide 3-kinase (PI3K)/serine-threonine kinase (AKT) signaling pathway, thereby promoting cell proliferation and inhibiting apoptosis ( Feng and Qiu, 2018 ; Wang et al, 2019 ; Wu et al, 2020 ). Meanwhile, KEGG enrichment analysis suggested that FTO is involved in the pathogenesis of CGN through PI3K/AKT signaling pathway ( Supplementary Figure S3B and Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the evidence collected so far, FOXOs may have both activating and inhibitory effects on fibrogenic processes, and Sirt1, as well as other sirtuins, such as Sirt2 and Sirt3, deacetylate FOXOs, thus favouring their nuclear translocation and FOXO-dependent gene expression. [117][118][119][120][121][122] In particular, in the context of fibrosis, the role of FOXO1 is still controversial, whereas FOXO3a, FOXO4 and FOXO6 have a profibrotic activity. 117-122…”
Section: Pi3k/akt and Mtor Pathwaysmentioning
confidence: 99%